Public sector innovation through nested experimental spaces: Reinventing the immigrant integration system - Tarabichi, Hani; Schildt, Henri; Kodeih, Farah (Research policy, 2025)
Our paper contributes to the growing scholarly discussion on public sector innovation by investigating how national governments can foster and direct change through initiatives that bridge the national and local government levels. We introduce the concept of a ‘nested experimental space’ to capture the government’s efforts to suspend established rules in a national experiment, while supporting the creation of local experimental spaces that foster the development and testing of diverse new practices. We conducted an inductive comparative study of three cities in the capital region of Finland that participated in a trial aimed at improving the integration of immigrants. Our findings highlight how each city’s motives and resources shaped the unique strategies for their local experimental spaces, leading to distinct approaches to experimentation and resulting in the cities assuming different roles within the broader field. Nested experimental spaces offer a promising approach to overcoming several limitations commonly associated with public sector innovation by linking together credible top-down policy innovation driven by ministries with bottom-up service innovation. •Nested experiments link top-down policy innovation and bottom-up experimentation•Governments enable experimentation by loosening constraints and providing resources•Actors enact own approaches to experimentation and local experimental spaces•Local experimental spaces drive diverse and complementary innovations•New practices diffuse horizontally across actors and vertically by shaping policy